Influence of structured reporting of tooth-colored indirect restorations on clinical decision-making - Berz Tamara; Möltner Andreas; Giraki Maria; Obreja Karina; Parvini Puria; Rüttermann Stefan; Gerhardt-Szép Susanne (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
The aim of the present study was to discover what influence structured reporting (study group = A) of toothcoloured lab-fabricated restorations has on clinical decision-making following international guidelines. By way of comparison, the conventional approach in the form of short reporting with 5 items (control group = B) was used as gold standard. The study was carried out in the first clinical semester of dentistry (n = 68) at the Goethe University in Frankfurt am Main. In the study group, indirect ceramic restorations were assessed on a scale of 1 (very good) to 5 (insufficient) using structured reporting (7 items, each with 5 subgroups) in accordance to World Dental Federation (FDI) - standards. Following this, the clinical decision on the insertion of the restoration was made. To evaluate the quality of the structured reporting, sensitivity, specificity, confidence intervals (Cl) and the respective predictive values (positive = PPV, negative= NPV) were determined. Based on FDI reporting, a ceramic inlay is also favored with a great degree of certainty in clinical decisions: this was the true in 34 procedures out of a total of 38 clinically incorporated ceramic inlays [sensitivity 67% (95% CI: 46%83%); specificity 89% (95% Cl: 75%-97%); PPV 82%, NPV 79%]. In the control group, sensitivity was 56% (95% CI: 35%-75%); specificity 92% (95% CI: 79%-98%); PPV 83%, NPV 74%. No significant differences could be determined between A and B (p = 0.813).  Due to the higher sensitivity and efficiency given comparable specificity, structured reporting of tooth-coloured lab-fabricated restorations based on FDI criteria, appears more recommendable than short reporting. It is also suitable for promoting decision-making in quality assessment, thus improving the durability of dental restorations.